Animal, vegetable, junk : a history of food, from sustainable to suicidal - Bittman, Mark (Houghton Mifflin Harcourt, 2021)
"From hunting and gathering to GMOs and ultraprocessed foods, this expansive tour of human history rewrites the story of our species-and points the way to a better future"--